2015
DOI: 10.1016/j.commatsci.2015.07.035
|View full text |Cite
|
Sign up to set email alerts
|

First principles study of normal and fast diffusing metallic impurities in hcp titanium

Abstract: a b s t r a c tThe diffusivities of metallic impurities in hexagonal close packed (hcp) Ti vary widely, with some species showing normal diffusion and others diffusing anomalously fast. Based on a transition-state theory model for impurity diffusion mediated by vacancies, self, and impurity interstitials, we find that the diffusion rate will be limited primarily by the formation energies of the various defects. We use density functional theory to calculate these defect energies, including the formation energie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
16
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 55 publications
(126 reference statements)
2
16
0
Order By: Relevance
“…This allows elements with relatively small metallic radius to dissolve both intrstitially and substitutionally. Fe, Co and Ni are indeed small relative to Ti, with metallic radii of R Fe =1.26Å, R Co =1.25Å, R Ni =1.24Å [9], which suggests these solute atoms could dissolve interstitially in Ti. Yoshida and co-workers were able to experimentally show that this is the case [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…This allows elements with relatively small metallic radius to dissolve both intrstitially and substitutionally. Fe, Co and Ni are indeed small relative to Ti, with metallic radii of R Fe =1.26Å, R Co =1.25Å, R Ni =1.24Å [9], which suggests these solute atoms could dissolve interstitially in Ti. Yoshida and co-workers were able to experimentally show that this is the case [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Some insight into what we expect for the behavior of impurities in Zr can be gained by considering recent studies quite similar to the present work of impurities in Ti, another hcp metal in the same column of the periodic table as Zr. Specifically, Bernstein et al calculated the formation energies to analyze the normal and fast diffusion of some solutes in HCP Ti [19] and Zhang et al identified the dominant diffusion mechanism for some solutes in HCP Ti [20] based on the calculated defect formation energies and migration energies. Both these studies suggest that smaller solutes are more likely to diffuse by interstitial mechanism, consistent with the Zr case.…”
Section: Introductionmentioning
confidence: 99%
“…Interstitials have important influences on various properties of materials [1][2][3][4][5][6]. Octahedral and tetrahedral interstitials are the mostly studied ones in metals and alloys so far [1,4,[6][7][8]. A crowdion is a kind of interstitial with an atom inserted between two neighboring matrix atoms along a close-packed direction, instead of at the center of an interstice; and its center of mass can easily move along that axis, according to simulations [9].…”
Section: Introductionmentioning
confidence: 99%
“…However, some large impurity atoms could diffuse even faster than small nonmetal atoms in hexagonal close packed (HCP) metals, such as Fe, Co and Ni in Ti and Zr [4]. The anomalously fast mobility of relatively large impurity metal atoms was attributed to an interstitial-mediated diffusion mechanism [1,4], which may have potential applications on synthesis and processing of materials. The addition of a thin Ni foil between two Ti plates to be joined was able to greatly improve the weld quality [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation